The impact of procedures of controlling the formation of the degrees of the proposed training load on the strength development in young basketball players - Khalaf, F. A. (Journal of Human Sport & Exercise, 2023)
The significance of this study is to enhance the game of basketball for the better and boost the muscle strength level suitable for the player to conduct the game needs according to the best control of appropriate loads, hoping to attain outcomes serving the game of basketball. The study objective is to prepare and control exercises in ways of forming the degrees of the proposed training load in developing the force characterized by speed and some offensive skills in youth basketball. To fulfil those aims, the experimental approach with two experimental groups is conducted to suit the solution of the research problem and achieve its objectives. The sample was selected purposively, represented by the young basketball players of South Oil Club, which were (12) Players. Based on the results, the exercises used according to the formation of the grades of the load (maximum - medium - less than the maximum) and the formation of degrees (less than the maximum - medium - less than the maximum), helped effectively in developing the strength characterized by speed and to develop some basic offensive skills with basketball. Formation of load grades (maximum - medium - less than maximum) is more favourable in creating the force characteristic of speed than forming degrees (less than the maximum - medium - less than the maximum), and this is an indication that this ability can merely be enhanced and developed in the maximum load degrees.